(untitled) (International Journal of Engineering Management Science, 2024)
This paper reviews recent progress in lithium-ion battery monitoring tailored for electric vehicles (EVs), essential for enhancing performance, safety, and longevity. It investigates novel methods including voltage/current monitoring, temperature tracking, and internal resistance assessment, as well as the significance of battery management systems (BMS). Challenges such as accuracy, integration, and sustainability are addressed, emphasizing the importance of predictive analytics and environmental responsibility. As EV adoption surges, addressing resource concerns and recycling becomes increasingly vital. The study highlights the necessity for ongoing innovation in battery monitoring to meet the evolving demands of the industry and expedite the shift towards sustainable transportation.